Capitalist Dreams, Posthuman Nightmares: AI and the Neoliberal Reordering of Humanity in Ian McEwan's Machines Like Me and Kazuo Ishiguro's Klara and the Sun - Benia, Amel; Dagamseh, Abdullah M. (Critique - Bolingbroke Society, 2025)
This article examines the portrayal of AI in Ian McEwan's Machines Like Me and Kazuo Ishiguro's Klara and the Sun through Deleuze and Guattari's framework of the twofold movement of capitalist deterritorialization and reterritorialization. It highlights how neoliberal capitalism leverages AI to create new markets, reinforces social inequalities, and ultimately alienates individuals from their communities and identities through processes of deterritorialization and reterritorialization. The commercialization of AI reflects capitalist dynamics, disrupts social interactions, and challenges human moral choices. The analysis reveals how AI contributes to technological divides, human displacement, and the creation of new territories of alienation and economic disparities. Both novels serve as cautionary tales, depicting dystopian futures where AI-driven automation leads to widespread unemployment and social unrest, highlighting the potential for AI to exacerbate existing inequalities. The novels expose the profit-driven promise of technological progress - particularly the allure of increased productivity and efficiency - and its impact on society. This paper emphasizes the urgent need for a critical reflection on the ethical and social implications of AI to ensure a more equitable and human-centered technological future.